Resource Strategies of Wild Plants - Craine, Joseph M., 1973- (Book collections on Project MUSE., 2009)
Over millions of years, terrestrial plants have competed for limited resources, defended themselves against herbivores, and resisted a myriad of environmental stresses. These struggles have helped generate more than a quarter million terrestrial plant species, each possessing a unique strategy for success. Yet, as Resource Strategies of Wild Plants demonstrates, the constraints on plant growth are universal enough that a few survival strategies hold true for all seed-producing plants. This book describes the five major strategies of growth for terrestrial plants, details how plants s.